Effect of yoga on autonomic nervous system function in females - Rika Kimoto; Isao Kambayashi; Akane Akizuki; Miku Tsukamoto; Munemitsu Fukushi; Akira Shionoya (Japanese Society of Physical Fitness and Sports Medicine, 2021)
The autonomic nervous system (ANS) maintains homeostasis through the balance of the sympathetic and parasympathetic subsystems or divisions. Currently, analysis of heart rate variability (HRV) offers an indirect, non-invasive assessment of ANS function. An irregular lifestyle and stress are known to affect ANS balance, influencing many diseases. Moreover, ANS disorder plays an important role in climacteric symptoms in menopausal females. The purpose of this study was designed to assess the effects of yoga practice sessions (herein referred to as "yoga") on ANS function and focused on the relationship between ANS function and subject age or personal history of yoga. A total of 113 healthy females participated in this study. They attended a 90-120 minute yoga practice session conducted by a well-qualified instructor. ANS function was assessed before and after the yoga practice session by HRV power spectral analysis. As a result, in females, yoga reduced fatigue by primarily improving sympathetic activity. In addition, the LnHF values tended to be increased after yoga only in the over-60y (60 years) group. Furthermore, there were individual differences in the amount of change in the sympathetic and parasympathetic activity values. In females with a low activity level before yoga, values were increased; whereas values decreased in females with a high activity value before yoga. In subjects with ≥5-year history of yoga, there was no significant correlation between the ANS parameters and subject age. Our study suggests that yoga for females supports well-balanced ANS function, and that the continuation of yoga over a period of time contributes to an improvement in ANS function.